Aspergillus spp. infection as a cause of acute exacerbations of chronic obstructive pulmonary disease: a prospective observational study - S., Lashmipriya; Chetambath, Ravindran; Sunny, Amitha; Shivashankaran, Sanjeev; Aslam, Muhammed (International Journal of Research in Medical Sciences, 2019)
Background: Majority of exacerbations of COPD (AECOPD) are due to infections. Usual agents causing AECOPD are gram negative bacteria, but rarely viruses and fungi are also implicated. However, the role of fungal infection, especially Aspergillus spp. in the clinical deterioration of COPD still remains unclear. This prospective observational study looks at the prevalence of aspergillus infection in AECOPD. The Objectives of this study were to analyse the prevalence and risk factors associated with Aspergillus infection in AECOPD, and to investigate the clinical outcomes. Methods: Patients admitted with AECOPD for a period of 3 months from 1st October 2017 to 31st December 2017 were prospectively included from ICU and general ward of Pulmonary Medicine department of a tertiary care hospital. Clinical, radiological and microbiological data were collected at admission and during the hospital stay. Clinical course and outcome are recorded. Results: There were 104 cases of AECOPD during the study period out of which 96 were males and 8 were females. 17 patients had evidence of aspergillus infection and diabetes was found to be an independent risk factor for aspergillus infection. Conclusions: Aspergillus infection is an important cause of COPD exacerbation and this is directly related to diabetes mellitus.